2018
DOI: 10.1002/term.2732
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion fracture healing: Evaluation of effectiveness of demineralized bone matrix and mesenchymal stem cells in a novel sheep bone nonunion model

Abstract: Nonunion treatment has a high rate of success, although recalcitrant nonunion may determine the need for amputation. Therefore, new treatment options are continuously investigated in order to further reduce the risk of nonunion recurrence. This study aimed to (a) develop a new large animal model for bone atrophic nonunion and (b) compare the efficacy of demineralized bone matrix (DBM) and DBM in combination with mesenchymal stem cells (MSC) in the new nonunion model. The new model consists of a noncritical, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Several cell types are involved in the dynamic modeling and remodeling process of bone tissue [6]. Among all the potential factors involved in bone metabolism, the differentiation capacity of bone marrow-derived mesenchymal stem cells (MSCs) is recognized to play quite a critical role [7][8][9]. Lineage specific differentiation of bone marrow stem cells is crucial to tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Several cell types are involved in the dynamic modeling and remodeling process of bone tissue [6]. Among all the potential factors involved in bone metabolism, the differentiation capacity of bone marrow-derived mesenchymal stem cells (MSCs) is recognized to play quite a critical role [7][8][9]. Lineage specific differentiation of bone marrow stem cells is crucial to tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our results demonstrated that MSCs and cortical bone graft with or without platelet growth factors were effective in accelerating non-union bone fracture healing in rabbits. However, there are a few studies concluded that stem cells had no significant effects on the healing process of non-union bone fractures (40).…”
Section: Discussionmentioning
confidence: 99%
“…This substitute derived from bones lacking mineral components while being rich in type I collagen and other growth factors [95,96,97,98]. Recently, Desai et al demonstrated that using demineralized bone matrices in association with bone marrow concentrate can increase the success of non-union treatment [99,100].…”
Section: Polymersmentioning
confidence: 99%